2022
DOI: 10.3390/vaccines11010049
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Messenger RNA Vaccines against SARS-CoV-2 Infection in Hemodialysis Patients: A Case–Control Study

Abstract: Patients with end-stage kidney disease (ESKD) are at increased risk for SARS-CoV-2 infection and its complications compared with the general population. Several studies evaluated the effectiveness of COVID-19 vaccines in the dialysis population but showed mixed results. The aim of this study was to determine the effectiveness of COVID-19 mRNA vaccines against confirmed SARS-CoV-2 infection in hemodialysis (HD) patients in the State of Qatar. We included all adult ESKD patients on chronic HD who had at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have shown that the booster dose of SARS-CoV-2 vaccines, especially mRNA-based vaccines, has proven to be relatively effective in providing protection against Omicron infection within the general population [ 40 42 ] (despite the vaccine evasion mentioned above). This benefit also extends to patients with kidney disease [ 43 – 46 ]. Notably, almost 50% of our patients received the third vaccine dose, which could partially account for the milder disease course observed compared to previous variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the booster dose of SARS-CoV-2 vaccines, especially mRNA-based vaccines, has proven to be relatively effective in providing protection against Omicron infection within the general population [ 40 42 ] (despite the vaccine evasion mentioned above). This benefit also extends to patients with kidney disease [ 43 – 46 ]. Notably, almost 50% of our patients received the third vaccine dose, which could partially account for the milder disease course observed compared to previous variants.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of mRNA vaccines against SARS-CoV-2 infection was estimated at 94.7% ≥ 14 days after the second dose. 16 On the other hand, vaccine effectiveness in kidney transplant recipients in Qatar against SARS-CoV-2 was estimated at 46.6% (95% CI: 0.0-73.7%) ≥ 14 days after the second dose and vaccine effectiveness against any severe, critical, or fatal COVID-19 disease was estimated at 72.3%. 17 …”
mentioning
confidence: 99%